Commodity Markets Outlook, April 2021 : Causes and Consequences of Metal Price Shocks - World Bank Group (World Bank, Washington, DC, 2021)
Commodity prices continued to recover in the first quarter of 2021 from lows reached in 2020, supported by the global economic recovery, improved growth prospects, and supply factors specific to crude oil, copper, and some food commodities. Looking ahead, oil prices are forecast to average $56/bbl in 2021, 36 percent higher than in 2020, and see a further rise to $60/bbl in 2022 as demand continues to recover. Metal prices are expected to average 30 percent higher in 2021 than in 2020 on the back of strong demand before dropping back somewhat in 2022. Agriculture prices are forecast to average nearly 14 percent higher in 2021, driven by a few food commodities, and are expected to stabilize thereafter. A Special Focus section examines the impact of metal price shocks on metal-exporting countries. Since global metal prices are predominantly driven by global demand shocks, metal price swings can amplify the impact of global downturns and recessions—or conversely, upturns—for metal exporters. Metal price jumps are associated with small, temporary gains from price increases for metal exporters, but metal price collapses tend to lead to larger, and longerlasting, output losses.